distribute
2x-10+7=3x-9
combine like terms
2x-3=3x-9
remove the variable completely from one side
-3=x-9
make sure the variable is alone
6=x
x=6 is the answer
2006-11-30 10:12:07
·
answer #1
·
answered by hobo h 4
·
1⤊
0⤋
6
2006-11-30 10:22:25
·
answer #2
·
answered by Joe 1
·
0⤊
0⤋
x=6
2006-11-30 10:17:51
·
answer #3
·
answered by mm12122472700 1
·
0⤊
0⤋
x=6
2006-11-30 10:14:00
·
answer #4
·
answered by Kris 2
·
1⤊
0⤋
2x - 10 + 7 = 3x - 9
2x - 3 = 3x - 9
2x - 2x - 3 + 9 = 3x - 2x - 9 + 9
6 = x.
2006-11-30 10:11:43
·
answer #5
·
answered by Amy F 5
·
1⤊
1⤋
2x-10+7=3x-9
2x-3x=-9+10-7
-x=-6
x=6
2006-11-30 10:13:12
·
answer #6
·
answered by Gucci_xoxo 2
·
1⤊
0⤋
Let me solve it step by step
Expand
2(x-5)=2x-10
2x-10+7=3x-9
2x-3=3x-9
Then,
-3=x-9
x=6
I think this is correct but I think you should double check my method.
2006-11-30 13:30:29
·
answer #7
·
answered by lulu 3
·
0⤊
0⤋
2(x-5)+7=3x-9
2x-10+7=3x-9
2x-3=3x-9
-3=x-9
6=x
2006-11-30 10:13:46
·
answer #8
·
answered by Will 1
·
1⤊
0⤋
x=-8
2006-11-30 10:11:02
·
answer #9
·
answered by ? 2
·
0⤊
3⤋